Pemberdayaan Masyarakat Melalui Kopi Lokal di Desa Winduaji Kecamatan Paguyangan Kabupaten Brebes Tahun 2019 - Siti Mubaedah; Ariesta Amanda; Chamid Sutikno; Indah Ayu Permana Pribadi; Zaula Rizqi Atika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study is a research in the field of Public Administration that aims to describe the conception of community empowerment in improving economic income through the development of local coffee products in Winduaji Village. The approach used is descriptive qualitative with a case study design. Research informants were selected using purposive sampling technique, with data sources including primary and secondary data. The focus of this research encompasses empowerment aspects that are oriented toward community needs, based on local potential, encouraging independence, environmentally oriented, and structurally based. The data analysis technique uses an interactive model. The research results show that the concept of community empowerment through local coffee development in Winduaji Village, Paguyangan District, Brebes Regency has been running quite well. This program has successfully increased community capacity in coffee processing and opened business opportunities through strengthening the identity of local coffee products with the branding